Pengaruh Budaya Organisasi dan Pengembangan Manajemen Sumber Daya Manusia pada Kantor Hukum Dedi Muliadi, S.H. & Rekan di Masa Pademi Covid-19 - Dedi Muliadi (Universitas Sains dan Teknologi Komputer, 2021)
All companies that have a business must always have competition, therefore every company must hold training and development for new and old employees. Because to make a company superior, sophisticated technology will not be enough because it will be useless if the technology is sophisticated but users or employees are not competent enough to use the technology. But the current situation is very different, because the virus is rampant in the world, not only in Indonesia, 200 other countries are also infected with the virus, this will certainly greatly affect the work system, teaching system and other systems. Company training and development are disrupted and methods must change with the aim of adapting training and development in a pandemic situation like this. The method used in this study uses qualitative methods and uses a literature review approach. Meanwhile, the target audience is companies that have started using new methods in training and development. By holding research like this, it is hoped that it can become an example for other companies in changing their training methods and development during a pandemic like today